Contemporary Review and Case Report of Botulinum Resistance in Facial Synkinesis. (28th December 2018) - Shinn, Justin R.; Nwabueze, Nkechi N.; Patel, Priyesh; Norton, Cathey; Ries, W. Russell; Stephan, Scott J.
Abstract : Background: Botulinum resistance poses significant treatment challenges for both patients and healthcare practitioners. We first present a case highlighting botulinum resistance in a patient who failed to respond to alternative formulations but who responded remarkably to incobotulinum toxinA, an identical toxin free of complexing proteins. Secondly, we provide a treatment algorithm and a review of the literature detailing clinical and immunochemical botulinum resistance. Results: Patients with botulinum resistance show a predisposition to failure on subsequent injections and possess a propensity toward neutralizing and nonneutralizing antibody development. The mechanisms of resistance are not entirely understood but thought to be secondary to an immunologic response. Risk factors for resistance include higher botulinum doses, more frequent injections, and high total lifetime dosage. Patients may still respond to other botulinum formulations or subtypes; however, this effect may be temporary. Conclusion: This case report describes a patient who responded to incobotulinum toxinA after failing treatment with the identical toxin compounded with buffer proteins, ultimately supporting the possibility of immune‐mediated resistance to the surrounding proteins and not the toxin itself. Often, impending treatment resistance is preceded by a poor or limited clinical response. Antibody testing is not indicated because it is neither sensitive nor specific and does not change clinical practice. Initially, higher doses of botulinum may overcome resistance without increasing treatment frequency, and side effects are far less common in those with clinical resistance. If higher dosages fail to produce a response, alternative botulinum formulations or subtypes can be considered. Laryngoscope, 129:2269–2273, 2019